Gynecologic Cancers in Pregnancy: Guidelines of an International Consensus Meeting. (1st May 2009) - Amant, Frédéric; Van Calsteren, Kristel; Halaska, Michael J.; Beijnen, Jos; Lagae, Lieven; Hanssens, Myriam; Heyns, Liesbeth; Lannoo, Lore; Ottevanger, Nelleke P.; Vanden Bogaert, Walter; Ungar, Laszlo; Vergote, Ignace; et al.
Abstract : Background: Gynecologic cancer during pregnancy is a special challenge because cancer or its treatment may affect not only the pregnant women in general but directly involve the reproductive tract and fetus. Currently, there are no guidelines on how to deal with this special coincidence. Methods: An international consensus meeting on staging and treatment of gynecological malignancies during pregnancy was organised including a systematic literature search, and interpretation followed by a physical meeting of all participants with intensive discussion. In the absence of large trials and randomized studies, recommendations were based on available literature data and personal experience thus representing a low but best achievable level of evidence. Findings: Randomized trials and prospective studies on cancer treatment during pregnancy are lacking. Gynecological cancer during pregnancy is a demanding problem, and multidisciplinary expertise should be available. Counseling both parents on the maternal prognosis and fetal risk is needed. When there is a firm desire to continue the pregnancy, gynecological cancer can be treated in selected cases. The staging and treatment should follow the standard approach as much as possible. Guidelines for safe pelvic surgery during pregnancy are presented. Mainly in cervical and ovarian cancer, chemotherapy and an alternative surgical approach need to be considered. Administration of chemotherapy during the second or third trimester may probably not increase the incidence of congenital malformations. Until now, the long-term outcome of children in utero exposed to oncological treatment modalities is poorly documented, but preterm birth on its own is associated with cognitive impairment. Delivery should be postponed preferably until after a gestational age of 35 weeks. Interpretation: Further research including international registries for gynecologic cancer in pregnancy is urgently needed. The gathering of both available literature and personal experience allowed only suggesting models for treatment of gynecologic cancer in pregnancy.